Capacity for the management of kidney failure in the International Society of Nephrology Latin America region: report from the 2023 ISN Global Kidney Health Atlas (ISN-GKHA) (2024)
Successful management of chronic kidney disease (CKD) in Latin America (LA) continues to represent a challenge due to high disease burden and geographic disparities and difficulties in terms of capacity, accessibility, equity, and quality of kidney failure care. Although LA has experienced significant social and economic progress over the past decades, there are still important inequities in health care access. Through this third iteration of the International Society of Nephrology Global Kidney Health Atlas, the indicators regarding kidney failure care in LA are updated. Survey responses were received from 22 of 31 (71%) countries in LA representing 96.5% of its total population. Median CKD prevalence was 10.2% (interquartile range: 8.4%–12.3%), median CKD disability-adjusted life year was 753.4 days (interquartile range: 581.3–1072.5 days), and median CKD mortality was 5.5% (interquartile range: 3.2%–6.3%). Regarding dialysis modality, hemodialysis continued to be the most used therapy, whereas peritoneal dialysis reached a plateau and kidney transplantation increased steadily over the past 10 years. In 20 (91%) countries, >50% of people with kidney failure could access dialysis, and in only 2 (9%) countries, people who had access to dialysis could initiate dialysis with peritoneal dialysis. A mix of public and private systems collectively funded most aspects of kidney replacement therapy (dialysis and transplantation) with many people incurring up to 50% of out-of-pocket costs. Few LA countries had CKD/ kidney replacement therapy registries, and almost no acute kidney injury registries were reported. There was large variability in the nature and extent of kidney failure care in LA mainly related to countries’ funding structures and limited surveillance and management initiatives.